2010
DOI: 10.1002/bip.21547
|View full text |Cite
|
Sign up to set email alerts
|

Bead size effects on protein‐mediated DNA looping in tethered‐particle motion experiments

Abstract: Tethered particle motion (TPM) has become an important tool for single-molecule studies of biomolecules; however, concerns remain that the method may alter the dynamics of the biophysical process under study. We investigate the effect of the attached microsphere on an illustrative biological example: the formation and breakdown of protein-mediated DNA loops in the lac repressor system. By comparing data from a conventional TPM experiment with 800 nm polystyrene beads and dark-field TPM using 50 nm Au nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Based on these calculations, we expect a ten-fold difference in loop formation rates between the AT rich and CG rich constructs -something that is clearly inconsistent with the experimental TPM data. We have previously ruled out bead effects, as we have shown that the presence of a large microsphere at the end of the DNA distorts loop formation kinetics at worst by a factor of two [17]. We also note that our results are in agreement with seemingly conflicting data from ring cyclization experiments and structural data from DNA-protein co-crystals.…”
Section: Resultssupporting
confidence: 88%
“…Based on these calculations, we expect a ten-fold difference in loop formation rates between the AT rich and CG rich constructs -something that is clearly inconsistent with the experimental TPM data. We have previously ruled out bead effects, as we have shown that the presence of a large microsphere at the end of the DNA distorts loop formation kinetics at worst by a factor of two [17]. We also note that our results are in agreement with seemingly conflicting data from ring cyclization experiments and structural data from DNA-protein co-crystals.…”
Section: Resultssupporting
confidence: 88%
“…Perhaps a more delicate aspect of this method regards temporal resolution [56] and data analysis: since all analysis approaches require time averaging, proper methods need to be adopted to obtain reliable kinetic parameters from TPM measurements [5759]. Another notable issue involves the steric effects of the tethered microsphere, which have been investigated both theoretically [60] and experimentally [61]. …”
Section: In Vitro Monitoring Of Facilitated Diffusion and Protein-mentioning
confidence: 99%
“…The discrepancy decreases with the bead size and this decrease is more significant for short tethers. This suggests that the observed reduction of the in-plane motion of the bead could also be related to some form of attractive DNA-bead interaction, such as that caused by the hydrodynamic effects discussed in [56]. All of the discrepancy sources mentioned above are systemic and unlikely to affect relative positions of RMS value nor the ratios of -factors associated with different loop types studied in the next section.…”
Section: Resultsmentioning
confidence: 86%
“…We believe that because of the loop-DNA steric effects, and the fact that all other intramolecular excluded volume effects and electrostatic interactions are taken into account, our results overestimate the mean (or RMS) end-to-end distances when compared to either experimental results, or other simulations in which some or all intramolecular interactions are not taken into account. This may suggest, that not only the bead volume exclusion effects that were analyzed in [61] and were taken into account in this work, are important, but also hydrodynamic effects [56] and possible steric attraction effects between the large bead and the DNA molecule may play a significant role and should be treated carefully in future models. Nonetheless, our results show qualitative agreement with both our experimental data and the results reported in [19] and support the existence of extended conformation of the Lac repressor.…”
Section: Discussionmentioning
confidence: 99%